PERKEMBANGAN METODOLOGI JARH WA TA’DIL: ANALISIS KOMPARATIF PADA YAHYA IBN MA’IN, AL-DZAHABI, DAN IBN HAJAR AL-‘ASQALANI - Nur Vita Ristiana; Azzahidi Azzahidi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
This study aims to analyze the development of the methodology of jarh wa ta‘dil by comparing the views of Yahya ibn Ma‘in, al-Dzahabi, and Ibn Hajar al-‘Asqalani. The background of this study lies in the fact that methodological understanding in hadith studies is still considered limited, as most existing hadith studies remain descriptive and have not yet emphasized comparative analysis of primary texts. This research employs a qualitative approach as well as a comparative-historical literature review. Data were collected through documentation of primary sources, namely Tarikh Ibn Ma‘in, Mizan al-I‘tidal, and Tahdzib al-Tahdzib, supported by secondary literature such as recent scholarly articles. The findings reveal that the methodology of jarh wa ta‘dil underwent transformation: Yahya ibn Ma‘in represented an empirical-individual approach, al-Dzahabi adopted a comparative-collective approach, and Ibn Hajar al-‘Asqalani developed a systematic approach. Through a method that compares primary texts and integrates a constructivist perspective in examining the development of hadith criticism methodology, this study enriches hadith scholarship, which constitutes its contribution. Practically, this research can serve as a foundation for critical and analytical hadith instruction.